Montelukast induces beneficial behavioral outcomes and reduces inflammation in male and female rats - Rostevanov, Ira S.; Betesh-Abay, Batya; Nassar, Ahmad; Rubin, Elina; Uzzan, Sarit; Kaplanski, Jacob; Biton, Linoy; Azab, Abed N. (Frontiers in Immunology, 2022)
Background. Accumulative data links inflammation and immune dysregulation to the pathophysiology of mental disorders; little is known regarding leukotrienes’ (LTs) involvement in this process. Circumstantial evidence suggests that treatment with leukotriene modifying agents (LTMAs) such as montelukast (MTK) may induce adverse neuropsychiatric events. Further methodic evaluation is warranted. Objective. This study aims to examine behavioral effects, as well as inflammatory mediator levels of chronic MTK treatment in male and female rats. Methods. Depression-like phenotypes were induced by exposing male and female rats to a chronic unpredictable mild stress (CUMS) protocol for four weeks. Thereafter, rats were treated (intraperitoneally) once daily, for two weeks, with either vehicle (dimethyl sulfoxide 0.2 ml/rat) or 20 mg/kg MTK. Following treatment protocols, behavioral tests were conducted and brain regions were evaluated for inflammatory mediators including tumor necrosis factor (TNF)-alpha, interleukin (IL)-6 and prostaglandin (PG) E2. Results. Overall, MTK did not invoke negative behavioral phenotypes (except for an aggression-inducing effect in males), yielding a generally safe behavioral profile. Numerous positive behavioral outcomes were observed, including reduction in aggressive behavior in females and reduced manic/hyperactive-like behavior and increased sucrose consumption (suggestive of antidepressant-like effect) in males. Furthermore, in control males, MTK increased IL-6 levels in the hypothalamus and TNF- in the frontal cortex, while in control females it generated a robust anti-inflammatory effect. In females that were subjected to CUMS, MTK caused a prominent reduction in TNF- and IL-6 in brain regions, whereas in CUMS-subjected males its effects were inconsistent. Conclusion. Contrary to prior postulations, MTK may be associated with select beneficial behavioral outcomes. Additionally, MTK differentially affects male vs. female rats in respect to brain inflammatory mediators, plausibly explaining the dissimilar behavioral phenotypes of sexes under MTK treatment.